Genotype – Environment Interaction and Stability Analysis in Tomato (Solanum lycopersicum L.) - TIWARI, ASHWINI KUMAR; LAL, GULSHAN (Indian Journal of Hill Farming, 2015)
Twenty five genotypes of tomato were evaluated in RBD with three replications under four environments to study the stability behavior of genotypes under the four environmental conditions created with different doses of plant bioregulators viz. NAA 50ppm (E1), GA + PCPA (combined) each 50ppm (E2), 2,4-D 5ppm (E3) and control (E4). Pooled analysis of variance exhibited significant mean squares due to genotypes for all the traits. There was enough variability due to environments for all the traits except plant height. Significant variation due to G x E interaction was observed for all the traits except fruit weight. Pant T-5 and ARTH-3 were found to be only desirable stable genotypes for fruit yield per plant. They can be used as parents in hybridization programme or could be suggested for planting under varying type of environments as specified in the present investigation.